Bee venom attenuates neuroinflammatory events and extends survival in amyotrophic lateral sclerosis models - Lee Myeong Soo; Hwang Hye Suk; Yang Sun Choel; Lee Sang Min; Jiang Jing Hua; Yang Eun Jin; Choi Sun-Mi (Journal of Neuroinflammation, 2010)
Abstract Background Amyotrophic lateral sclerosis (ALS) is a disease affecting the central nervous system that is either sporadic or familial origin and causing the death of motor neurons. One of the genetic factors contributing to the etiology of ALS is mutant SOD1 (mtSOD1), which induces vulnerability of motor neurons through protein misfolding, mitochondrial dysfunction, oxidative damage, cytoskeletal abnormalities, defective axonal transport, glutamate excitotoxicity, inadequate growth factor signaling, and neuroinflammation. Bee venom has been used in the practice of Oriental medicine and evidence from the literature indicates that BV plays an anti-inflammatory or anti-nociceptive role against inflammatory reactions associated with arthritis and other inflammatory diseases. The purpose of the present study was to determine whether bee venom suppresses motor neuron loss and microglial cell activation in hSOD1G93A mutant mice. Methods Bee venom (BV) was bilaterally injected (subcutaneously) into a 14-week-old (98 day old) male hSOD1G93A animal model at the Zusanli (ST36) acupoint, which is known to mediate an anti-inflammatory effect. For measurement of motor activity, rotarod test was performed and survival statistics were analyzed by Kaplan-Meier survival curves. The effects of BV treatment on anti-neuroinflammation of hSOD1G93A mice were assessed via immunoreactions using Iba 1 as a microglia marker and TNF-α antibody. Activation of ERK, Akt, p38 MAP Kinase (MAPK), and caspase 3 proteins was evaluated by western blotting. Results BV-treated mutant hSOD1 transgenic mice showed a decrease in the expression levels of microglia marker and phospho-p38 MAPK in the spinal cord and brainstem. Interestingly, treatment of BV in symptomatic ALS animals improved motor activity and the median survival of the BV-treated group (139 ± 3.5 days) was 18% greater than control group (117 ± 3.1 days). Furthermore, we found that BV suppressed caspase-3 activity and blocked the defects of mitochondrial structure and cristae morphology in the lumbar spinal cord of hSOD1G93A mice at the symptomatic stage. Conclusion From these findings, our research suggests BV could be a potential therapeutic agent for anti-neuroinflammatory effects in an animal model of ALS.